George P. Brown, The Charter and Ordinances of the City of Marquette 213 (1898) - (:unkn) unknown (My University, 1887)
§ 875: It shall be unlawful for any person, except officers of the peace and night-watches legitimately employed as such, to go armed with a dirk, dagger, sword, pistol, air-gun, stiletto, metallic knuckes, pocket-billie, sand-bag, skull-cracker, slung-shot, razor, or other offensive and dangerous weapon or instrument concealed upon his person.
Keywords: CARRY - CONCEALED